Educational quality in preschool education: Innovations and best practices - Portocarrero Espinoza, Deyssy Jaquelini (2025)
This article presents a study on preschool education as the fundamental foundation for the comprehensive learning and development of children, providing the necessary conditions for them to thrive fully. Its purpose is to analyze and describe quality education at the initial level, given its critical importance in children's cognitive, social, socioemotional, and physical growth. The research employs a basic qualitative approach, using a systematic review design of articles, texts, and documents on the subject. Among the key findings, the initial education curriculum offers guidelines that enhance pedagogical practice, ensuring quality education through a child-centered, holistic approach that respects diversity and promotes children's full development in their early years. Educators must consider these principles to design and implement effective learning experiences that support children's holistic development. The state guarantees education quality through Law 28044, the General Education Law (Articles 8 and 13), which emphasizes quality education at all levels while fostering autonomy, creativity, and critical thinking development. In conclusion, early childhood education requires innovation and best practices, adapted to the needs and characteristics of each context. Advances in neuroscience, technology, and pedagogy enable the identification of new strategies and approaches to ensure quality education from the earliest years of life.